Literature Study of The Effect of Aluminum Doped ZnO Nanoparticles on Structure and Gap Energy - Muchamad Anjar Fadillah; Heru Harsono; Mauludi Ariesto Pamungkas (Lembaga Pengembangan Kinerja Dosen, 2025)
Nanomaterials have a variety of uniqueness and attractiveness, it is considered necessary to carry out literature study, beside the laboratory investigation, among others, on the nanoparticle structure and energy gap of ZnO nanoparticles doped with aluminum (Al) resulting from synthesis using various methods. In this study, the structure of the nanoparticles was divided into three types, namely crystal structure, crystallite size, and morphology. The crystal structure of the Al doped ZnO nanoparticles is hexagonal wurtzite. It is found, that, a decrease in crystallite size occurs as the doping of Al into ZnO increases to its solubility limit. A similar pattern also occurs in particle size. The high concentration of Al doping results in agglomeration. The morphology of Al doped ZnO nanoparticles in some references of this study are rod, spherical, and irregular spheres. The energy gap value of Al doped ZnO nanoparticles increases with the increasing concentration of Al doping in ZnO. So, it can be said, that Al as a doping material has an influence on the structure and optical properties of ZnO nanoparticles.